Utilization and Outcomes of Children Treated with Direct Thrombin Inhibitors on Paracorporeal Ventricular Assist Device Support. Issue 8 (August 2020) - VanderPluym, Christina J.; Cantor, Ryan S.; Machado, Desiree; Boyle, Gerald; May, Lindsay; Griffiths, Eric; Niebler, Robert A.; Lorts, Angela; Rossano, Joseph; Sutcliffe, David L.; Lytrivi, Irene D.; Buchholz, Holger; et al.
Abstract : Thrombotic and bleeding complications have historically been major causes of morbidity and mortality in pediatric ventricular assist device (VAD) support. Standard anticoagulation with unfractionated heparin is fraught with problems related to its heterogeneous biochemical composition and unpredictable pharmacokinetics. We sought to describe the utilization and outcomes in children with paracorporeal VAD support who are treated with direct thrombin inhibitors (DTIs) antithrombosis therapy. Retrospective multicenter review of all pediatric patients (aged <19 years) treated with a DTI (bivalirudin or argatroban) on paracorporeal VAD support, examining bleeding and thrombotic adverse events. From May 2012 to 2018, 43 children (21 females) at 10 centers in North America, median age 9.5 months (0.1–215 months) weighing 8.6 kg (2.8–150 kg), were implanted with paracorporeal VADs and treated with a DTI. Diagnoses included cardiomyopathy 40% (n = 17), congenital heart disease 37% (n = 16; single ventricle n = 5), graft vasculopathy 9% (n = 4), and other 14% (n = 6). First device implanted included Berlin Heart EXCOR 49% (n = 21), paracorporeal continuous flow device 44% (n = 19), and combination of devices in 7% (n = 3). Adverse events on DTI therapy included; major bleeding in 16% (n = 7) (2.6 events per 1, 000 patient days of support on DTI), and stroke 12% (n = 5) (1.7 events per 1, 000 patient days of support on DTI). Overall survival to transplantation (n = 30) or explantation (n = 8) was 88%. This is the largest multicenter experience of DTI use for anticoagulation therapy in pediatric VAD support. Outcomes are encouraging with lower major bleeding and stroke event rate than that reported in literature using other anticoagulation agents in pediatric VAD support. Abstract : Supplemental Digital Content is available in the text.